The Influence of Brand Image, Service Quality, and Social Media Marketing on Purchase Decision at Restaurant Navy Seals Surabaya - Sarah Wahyu Darmawan Geraldine Putri; Sengguruh Nilowardono (Quantitative Economics and Management Studies, 2021)
Restaurant Navy Seals Surabaya has many determinants in purchasing decisions, these factors are Brand Image, Service Quality, Social Media Marketing. And these factors will be examined statistically which aims to determine how much influence. The variables used are four, namely Brand Image (X1), Service Quality (X2), Social Media Marketing (X3), and Purchase Decision (Y). Data collection was obtained from distributing questionnaires to customers of Restaurant Navy Seals Surabaya. The results show that the Brand Image variable (X1), Service Quality (X2), and Social Media Marketing (X3) simultaneously and partially have a significant effect on Purchase Decision (Y). This research is a quantitative study with a sample of 160 respondents. The analysis technique used is multiple linear regression analysis. Based on this research, Restaurant Navy Seals Surabaya can maintain Brand Image, Service Quality, and Social Media Marketing, so that customers survive and faithfully buy at the place.